Effects of renal denervation on heart failure biomarkers and blood pressure in patients with resistant hypertension. (August 2016) - Neumann, Johannes Tobias; Ewen, Sebastian; Mortensen, Kai; Nef, Holger; Zeller, Tanja; Ojeda, Francisco; Sydow, Karsten; Mahfoud, Felix; Böhm, Michael; Hamm, Christian; Dörr, Oliver; Blankenberg, Stefan
Aim: This multicenter study investigated the effect of renal denervation therapy (RDN) on the heart failure related biomarkers NT-proBNP, ST-2, galectin-3 and hs-TnI.Patients & methods: We included 157 patients with resistant hypertension undergoing RDN. Blood sampling was performed before and 6 months after RDN.Results: Six months after RDN systolic blood pressure (BP) was reduced by 24 mmHg. Biomarker concentrations were not changed after RDN, except a small increase of hs-TnI by 0.3 pg/ml. In individuals with high baseline BP, we observed a BP reduction of 45 mmHg and a decrease of hs-TnI concentrations by 1.2 pg/ml.Conclusion: In this multicenter analysis RDN did significantly reduce systolic BP. However, NT-proBNP, ST-2, galectin-3 and hs-TnI did not correspond to BP reduction 6 months after RDN.